Factors Related To The Event Of Chronic Energy Lack (Kek) In Pregnant Women At Puskesmas Pematang Pansggang I Regency Of Ogan Komering Ilir (Oki) In 2021 - Ruqiya Hazirotul Qudsiya; Sendy Pratiwi Ramadhani; Turiyani (Science Midwifery, 2022)
Chronic energy deficiency (CED) is a pregnant woman who has an upper arm circumference (LILA) < 23.5 cm. At Pematang Panggang I Health Center, pregnant women who experience Chronic energy deficiency (CED) in pregnancy in 2018 was 38 people, in 2019 it was reduced to 34 people, and in 2020 even more increased to 36 people. This study aims to determine the relationship between age, parity, education and occupation with the incidence of Chronic Energy Deficiency (KEK) in pregnant women. The method used is an analytical survey with a cross-sectional approach part. With a population of 503 pregnant women who experience a lack of energy chronicles (KEK) at Pematang Panggang I Health Center. Samples were taken using Slovin formula with random sampling technique as many as 224 samples. Research result shows that there is a relationship between age and the incidence of chronic energy deficiency in pregnant women (P = 0.002), there is a relationship between parity with the incidence of chronic energy deficiency in pregnant women (P = 0.039), there was a relationship between history of education with the incidence of chronic energy deficiency in pregnant women (P = 0.002), and there is no relationship between work and the incidence of chronic energy deficiency in pregnant women (P = 0.492). There is a relationship between age, parity and education with the incidence of chronic energy deficiency in pregnant women and there is no relationship between work and the incidence of chronic energy deficiency in pregnant women. Suggestion in the promotive-preventive efforts of chronic energy deficiency in pregnant women education is prioritized for at-risk groups